Wristop - Market Selection for Medical Technologies - Malinen, Pasi; Cooney, Thomas (Piccola Impresa / Small Business, 2012)
Having missed the opportunity to manufacture wrist computers for Suunto’s competitors, the founders of Wristop started to look for alternative opportunities where mobile transmission, design and wrist computers could be used. They were seeking a match between wrist computers and various end-user sectors. The Wristop team wanted to change the direction of the company due to external (previous employer Suunto was threatening the company with law suits) and internal pressures. However, deciding what strategy they should take was proving a difficult decision. Over coffee with a medical doctor friend of his, Matti Aalto-Setälä (the CEO of Wristop) started to brainstorm ideas with him of employing wrist computers for medical use. After this initial meeting and idea generation, the company organised another brainstorming session with a group of physicians. The question the CEO was addressing was, “For what medical purpose could a patient use a wrist computer?” In the brainstorming session, it was noted that the medical technology sector has a small number of dominant manufacturers, but is a growing and lucrative sector. Thus, the company decided to explore an alternative market in the medical technology industry. However, there were many opportunities within different segments of the market and Matti and his co-founders could not decide which one was the most attractive on a long-term basis and what market entry strategy should they use.